Methylobacterium infection of an arthritic knee. (29th January 2019) - Beck, Eric T.; Bateman, Allen C.; Maccoux, Darin
Abstract : Introduction. Osteoarthritis (OA) is a common cause of knee pain in older adults. OA is primarily caused by deterioration of cartilage in the knee, which decreases the ability of synovial fluid to absorb shock and increases the opportunity for bones of the joint to rub together. Hylan G-F 20 (Synvisc-One) is a compound that can be injected directly into the knee to help combat the pain associated with OA by lubricating and cushioning the joint. Case presentation. A 92-year-old male reported to his primary care provider with complaints of pain due to OA. An ultrasound-guided injection of Hylan G-F 20 was administered without complication; however, the patient presented to an emergency department approximately 10 h after the injection complaining of stabbing pain and swelling in the same knee. Specimens submitted for culture 12 h post-injection yielded a Methylobacterium spp. that was identified following biochemical testing, MALDI-TOF (matrix-assisted laser desorption/ionization-time of flight) MS analysis and bacterial sequencing. Interestingly, symptoms began to subside following aspiration of synovial fluid, and new cultures of synovial fluid collected 24 h post-Hylan G-F 20 injection were negative for the presence of Methylobacterium . The patient's knee returned to baseline with diminished pain due to OA approximately 1 week after the initial injection without antibiotic treatment. Conclusion. We report short-term complications following treatment of OA with a Methylobacterium -contaminated lot of Hylan G-F 20.